The Effectiveness of Academic Buoyancy Training on Academic Burnout, Self-Destructive Behavior, and Thought Control Strategies in High School Students - Seifi, Saeb; Jahan, Faezeh; Sotoudeh Asl, Nemat; Rezaei, Noor Mohammad (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to evaluate the effectiveness of academic buoyancy training in reducing academic burnout, self-destructive behaviors, and enhancing thought control strategies among high school students. Methods and Materials: A quasi-experimental design with a pre-test, post-test, and follow-up was employed, involving 60 female high school students from District 2 of Karaj city during the 2022-2023 academic year. Participants were randomly assigned to either the academic buoyancy training group (n= 15) or the control group (n= 15). The intervention consisted of 12 sessions of academic buoyancy training. Data were collected using the Academic Burnout Questionnaire, Cunningham’s Self-Destructive Behavior Scale, and the Wells and Davies Thought Control Questionnaire. Data analysis included ANCOVA to assess the effectiveness of the intervention, with assumptions of normality, homogeneity of variances, and linearity confirmed. Findings: The results demonstrated significant reductions in academic burnout, self-destructive behaviors, and improvements in thought control strategies in the training group compared to the control group. Specifically, academic burnout scores decreased from M= 53.6 (SD= 8.2) in the pre-test to M= 39.4 (SD= 6.3) in the post-test (p < .001, η²= .724). Self-destructive behavior scores reduced from M= 102.7 (SD= 14.4) to M= 87.2 (SD= 11.9) (p < .001, η²= .627), and thought control strategies improved from M= 68.4 (SD= 10.3) to M= 50.3 (SD= 7.9) (p < .001, η²= .614). Conclusion: Academic buoyancy training significantly reduces academic burnout and self-destructive behaviors while enhancing thought control strategies among high school students. These findings suggest that academic buoyancy training is an effective intervention to promote psychological resilience and academic success in adolescents.